Toward a Theory of Black Deaf Feminism: The Quiet Invisibility of a Population. Issue 2 (May 2019) - Chapple, Reshawna L.
This article considers ways to enhance the conceptualization of Black deaf women's lived experiences through an intersectional lens. An intersectional framework places emphasis on how social constructions of blackness, gender, and deafness shape the identity and experiences of Black deaf women. To outline the need for such a theory, this article first examines social constructions of Black deaf women in the intersections of race, gender, and deafness in comparison to current research. Second, I discuss the relevancy of social theories (i.e., critical race feminism, feminist disability theory, and theoretical approaches prominent in critical deaf studies) in providing a conceptual framework for an analysis of identity in relation to race, gender, and disability. Finally, I introduce the tenants of Black Deaf feminism and discuss the ways Black Deaf feminism enhances intersectionality by centering the lived experience from the standpoint of Black deaf women.